Hysterosalpingography (HSG), hysteroscopy and laparoscopic evaluation of female genital tract of patient attending tertiary infertility centre and correlation of various modalities - Maiti, G. D.; Lele, Prasad (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Hysterosalpingogarphy (HSG) has traditionally been the first line of investigation anatomy and contour of uterine cavity along with fallopian tube and its patency. Because of limitations of HSG, video endoscopic evaluation of endometrial and peritoneal cavity by diagnostic hysteroscopy and laparoscopy can diagnose many subtle and obvious pathologies in evaluation of infertile couple. To know this difference author studied the efficacy of HSG along with diagnostic laparohysteroscopy. Methods: HSG, Diagnostic Hysteroscopy and Laparoscopy were performed on a group of 50 Patient of primary and secondary infertility. Findings of HSG, Hysteroscopy and Laparoscopy were computed, analyzed and corelated. Results: HSG showed a false positive rate of 25% for tubal factor and false negative 12% for uterine factors when compared with hysteroscopic and laparoscopic findings. The sensitivity of HSG was 75% and specificity was 88 % when compared with Hysteroscopic and Laparoscopic findings. Among various abnormality detected during the present study were, congenital anomaly 7(14%), Asherman syndrome 5 (10%), Tubal factor defect 6(12%), fibroid 3(6%) and Pelvi-inflammatory disease in 7(14%) of cases. Conclusions: Though HSG is a simple procedure for detecting abnormality of female genital tract, due to its low specificity and sensitivity hysterolaparoscopy should be complemented during infertility work up in all patient.